A methodology to transform business goals and objectives into software requirements - Čaplinskas, Albertas (Lietuvos matematikos rinkinys, 2007)
The paper proposes a methodologyhow to transform business goals and objectives into supportingsoftware requirements. The proposed approach is based on ideas beyond the Zachman’s framework. However both lines and columns of the Zachman’s framework are interpreted in quite different way. The left column of the proposed framework is Why column. At the top level it describes business goals and objectives. Other columns are interpreted in the way allowing formulating requirements that step-by-step can be flowdown into detailed and measurable software requirements. For example, the Who column associates business goals  and subgoals with the particular roles (positions) that in some way contribute to their implementation and for each role describes performing business tasks. User interface requirements and usability requirements are derived later from this information. The main advantage of the proposed methodology is the possibility to ensure better strategic alignment of software requirements.
Keywords: strategic alignment; requirements engineering; requirements flowdown